Persembahan Persepuluhan Menurut Maleakhi 3:6-12 - Binar, Sri; Koeswono, Edwin Sucipto; Koeswono, Olivia Sharon (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This research discusses the tithe offering according to Malachi 3:6-12, which is one of the topics with a high level of complexity, resulting in various interpretations. Tithing is also a highly sensitive issue in the lives of believers in relation to the church, causing controversies and even divisions. The method used is topical/theological exegesis with an emphasis on contextual-historical analysis. As a result, it is found that tithing is one of God's commands for the nation of Israel who deviated from the Torah law. Regarding the location of tithing, it is the house of God, which in the Old Testament refers to a place within the house of God, but nowadays it can refer to the church, organizations, or individuals in need, not limited to the local church, as long as it is to advance the work of God and not for the personal interests of the recipient. The purpose or result of obedience in giving tithes is gratitude and the glorification of God's name. Tithing represents a discontinuity because believers today do not live under the Torah law, but under the grace of God through the death of Christ.